Interoperability Strategy Of The Indonesian National Armed Forces And National Police In Securing National Food Resources Through A Holistic Security Approach - Pria Budi; Rudy Sutanto; Sigit Purwanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Food security is a vital component of national stability, particularly amid multidimensional threats such as climate change, land-use conversion, and illegal food distribution. Riau Province faces serious food security vulnerabilities due to environmental degradation, frequent forest and land fires, and a strong dependence on external food supplies. These conditions highlight the urgent need for an integrated food security strategy supported by synergy among defense and security institutions. This study analyzes the interoperability strategy between the Indonesian National Armed Forces (TNI) and the Indonesian National Police (Polri) in securing national food resources through a holistic security approach, with a specific focus on Riau Province and Pekanbaru City. Using a qualitative descriptive method and a case study approach, the research incorporates policy analysis, literature review, and secondary data from government agencies. The findings indicate that TNI–Polri coordination remains fragmented and lacks a structured interoperability mechanism. Key challenges include weak policy alignment, limited data sharing, and insufficient technological support for monitoring. Nevertheless, synergy opportunities exist through establishing a joint command center, developing technology-based food intelligence systems, and strengthening cross-sectoral regulatory frameworks. Overall, a holistic TNI–Polri interoperability strategy offers a strategic pathway to reinforce food security and enhance national resilience against non-traditional threats